2000
DOI: 10.3109/02770900009055465
|View full text |Cite
|
Sign up to set email alerts
|

Serum Eosinophil Cationic Protein for Predicting the Prognosis of a Step-Down in Inhaled Corticosteroid Therapy in Adult Chronic Asthmatics

Abstract: We investigated whether the serum concentration of eosinophil cationic protein (s-ECP) can be used to determine when a step-down in inhaled corticosteroid therapy is indicated for patients with chronic asthma. A total of 24 adult patients, whose symptoms were well controlled with inhaled beclomethasone dipropionate (iBDP), were studied. The dosage of iBDP was reduced by half once a month until the dose reached one-quarter of the original level. s-ECP and blood eosinophil counts were determined once a month bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
2
7
1
Order By: Relevance
“…The rate of exacerbation within 3 months of the initial step down was higher in group B patients (45.5%) than in group A patients (23.1%), although the difference was not statistically significant. We have reported previously that a high level of sECP may indicate an increased risk of exacerbation within a short‐term clinical course after a step down in iBDP therapy 6 . The results in the present study confirm these previous findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The rate of exacerbation within 3 months of the initial step down was higher in group B patients (45.5%) than in group A patients (23.1%), although the difference was not statistically significant. We have reported previously that a high level of sECP may indicate an increased risk of exacerbation within a short‐term clinical course after a step down in iBDP therapy 6 . The results in the present study confirm these previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…Several lines of evidence indicate that theophylline contributes to asthma control by affecting eosinophil‐relevant airway inflammation 14–17 . We examined the short‐term prognosis of a step down in iBDP therapy among patients taking oral theophylline and found that sECP still rose following the step down 6 . Furthermore, we reported that sECP levels in asthmatics did not change significantly after withdrawal of theophylline 18 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding is in contrast to our previous finding that sECP before a step down in iBDP therapy was significantly higher in patients when the step down was successful than when it was unsuccessful (6,7). Furthermore, the finding in the present study that significant fluctuation in EOS or sECP was not observed even during symptom deterioration also differed from the results obtained in our previous study (7).…”
Section: Reprintscontrasting
confidence: 86%
“…However, the mechanisms of these actions remain unclear, unlike corticosteroid, which is known to be only an anti-inflammatory agent. We previously performed long-term consecu- tive measurement of the serum concentration of eosinophil cationic protein (sECP) in adult asthmatics, and reported that in mild to moderately persistent asthmatics whose symptoms were well controlled by 400-800 mg inhaled beclomethasone dipropionate (iBDP)/day, sECP is a useful indicator of the requirement for a step down in iBDP therapy (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%